Performance evaluation of geospatially assisted reference evapotranspiration models - Pandi, Dinagarapandi; Saravanan, Kothadaramanan; Kuppusamy, Mohan; Birasnav, M. (Arabian Journal of Geosciences, 2022)
Mapping of spatiotemporal distribution of evapotranspiration becomes important for sustainable water management as water scarcity is nowadays a growing concern in almost all the continents. In general, researchers estimate evapotranspiration by multiplying the computed reference evapotranspiration (ETo) with the corresponding crop coefficient. Such estimation of ETo requires data related to spatiotemporal meteorological and vegetation field characteristics, and however, these data are rarely available in most developing countries such as India. Thus, researchers constantly develop various methods and evaluate the applicability of these methods to accurately capture spatiotemporal distribution. The purposes of this study are to (a) examine the applicability of Hargreaves and MODIS ETo method to map the spatiotemporal distribution over Thamirabarani basin located in Southern India and (b) evaluate the performances of Hargreaves and MODIS ETo methods and compare it to FAO 56 Penman–Monteith method. To achieve these purposes, ETo data of Hargreaves method and MODIS ETo method over Cheranmadevi meteorological observatory are extracted and performances of these methods are compared with FAO 56 Penman–Monteith method. Results show that a match exists among all the three ETo datasets, and no major deviations have been observed. However, this study suggests local calibration of Hargreaves and MODIS ETo method as considerable mismatch has been observed at ETo daily value. Overall, the conclusion of this study encourages the application of the Hargreaves method and MODIS ETo method in developing countries, where the data shortage condition prevails.
Keywords: Evapotranspiration; FAO 56 Penman–Monteith method; Hargreaves method; MODIS ETo; Thamirabarani basin; dept.mgt; peer-reviewed

Green supply chain management: A theoretical framework and research directions - Birasnav, M.; Chaudhary, Richa; Henry Dunne, James; Bienstock, Joshua; Seaman, Cristina (Computers & Industrial Engineering, 2022)
Practitioners and academicians dedicate significant attention to tackling initiatives and executing mechanisms to address society’s environmental concerns. Further, organizations and researchers recognize that there is a need to implement green supply chain management (GSCM) practices as a part of green strategy. To date, embedding a sustainability dimension into supply chain management remains a challenge for organizations given the lack of systematic knowledge of the key dimensions of GSCM practices, the factors that influence the implementation of GSCM practices, and the benefits that organizations gain through the implementation of such practices. To address this problem, this study reviews 151 research articles published between 1997 and 2021 in the GSCM literature, and offers a theoretical framework that synthesizes and integrates the knowledge acquired from the reviewed literature. This framework includes various dimensions of GSCM practices identified in the past research studies, the antecedents that influence implementation of GSCM practices, and the outcomes of implementation of such practices. Further, this study offers theoretical and practical perspectives to support future research utilizing a research model as a baseline to guide organizations in the understanding of the primary GSCM attributes, their predictors, and benefits.
Keywords: Antecedents; Green supply chain; Outcomes; Systematic literature review; dept.mgt; peer-reviewed

Total quality leadership and organizational innovativeness: the role of social capital development in American schools - Birasnav, M.; Gantasala, Swapna Bhargavi; Gantasala, Venugopal Prabhakar; Singh, Abhishek (Benchmarking: An International Journal, 2022)
Purpose The purpose of this study is to explore the relationship between total quality leadership, social capital development and organizational innovativeness in the school environment. While there are research studies focused on the impact of leadership on implementing quality management practices, innovation and organizational performance, the mediating effect of social capital development has not been explored on the influence of the school leaders. Design/methodology/approach To achieve the purpose of this study, data collected from 158 principals, who participated in the Teaching and Learning International Survey 2018, were analyzed using structural equation modeling. Findings This study found that total quality learning-oriented school leaders are supportive of developing social capital in their schools, and such social capital development is very useful to improve organizational innovativeness. Interestingly, social capital development has been found to mediate the relationship between total quality learning-oriented school leadership and organizational innovativeness. Practical implications This study submits evidence for two major activities that school leaders perform: learning- and control-oriented activities, both being important for improving and measuring quality in the educational sector. This study clearly shows that control-oriented activities lean toward negatively on social capital while learning-oriented activities strongly and positively influence social capital development. From this study, practitioners can be aware and consciously promote social capital development in schools and that social capital development mediates the influence of total quality leadership and innovation in schools. Originality/value Schools can be visualized as guarded communities for creating a secure environment for students in support of learning. This research study shows that the combined cognitive capital, structural capital and relational capital mediate the impacts of total quality leadership on innovativeness in schools. Thus, school leaders should first establish a mechanism to develop social capital among their employees to bring up innovative initiatives.
Keywords: Organizational innovativeness; School leaders; Social capital; TALIS; Total quality leadership; dept.mgt; peer-reviewed

Home Address Exemptions in State FOI Laws - Gil, Jodie; Smith, Robert A.; Badr, Kauther S. (The Journal of Civic Information, 2022)
Keywords: dept.mgt; peer-reviewed

The Evolving Landscape of International Consumer Data Privacy Compliance. - Pisano, Mark; Smith, Robert A.; Badr, Kauther S. (ACET Journal of Computer Education & Research, 2022)
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Introduction to Business Law and Ethics - Badr, Kauther S.; Smith Jr, Robert A. (Kendall Hunt, 2022)
Keywords: dept.mgt

A Longitudinal Investigation of the Changes in Work Motivation and Employees’ Psychological Health - Wang, Zheni; Panaccio, Alexandra (Administrative Sciences, 2022)
Organizations strive to motivate employees to thrive at work. However, employees’ motivation is likely to vary over a short period (e.g., a few months) to cope with the routine dynamics of organizations’ activities. These motivation dynamics covary with employees’ affective, cognitive, and behavioral outcomes in the workplace. Moreover, employees’ psychological health, a multidimensional concept focused on the individual’s well/ill-being simultaneously, changes over time. Using the integrated theoretical frameworks of self-determination theory (SDT) and the hierarchical model of self-determined motivation (H-SDT), this research sought to examine the motivational changes following the dual-path model. In particular, this work sought to unpack the temporal dynamics in employees’ subjective well/ill-beings predicted by the changes in basic needs satisfaction/frustration through autonomous/controlled motivation, while considering the characteristics of people’s general causality orientations (trait-level motivation). Over four months, longitudinal field data were collected from the employees in several private small businesses in the consumer product retail industry. Latent growth modeling (LGM) results supported the positive dual relations between the changes in employees’ psychological health and basic psychological needs satisfaction/frustration, but neither the changes of autonomous/controlled work motivation nor the indirect change paths via autonomous/controlled work motivation were significant. Finally, we discussed the theoretical and practical implications of the findings. Limitations and possible future research directions to further this line of research on the dynamic of work motivation were also summarized.
Keywords: change in motivation; dept.mgt; longitudinal study; peer-reviewed; psychological health

Energy transitions and labor market patterns in the U.S. coal industry - Michieka, Nyakundi M.; Graziano, Marcello; Musso, Marta; Fouquet, Roger (Structural Change and Economic Dynamics, 2022)
The U.S. coal industry is in the midst of a transition. Changes in regulation and technological innovation from other fossils and renewables have affected its competitiveness. These could have significant impacts on the labor market where jobs could be lost. In this study, we investigate how changes in employment in the coal industry affect wages in 20 industries in 10 U.S. coal producing states. We assess how these transitions impact welfare programs, since coal producing regions are associated with higher poverty levels. Results show that in the long run, migration of coal workers decreased wages in the construction, manufacturing sectors. Point estimates reveal that an increase in separations of coal workers increase Supplemental Nutrition Assistance Program (SNAP) caseloads. In states where coal mining has a smaller contribution to GDP, an increase in coal employment increases SNAP caseloads.
Keywords: Labor market dynamics; dept.mgt; peer-reviewed

The spatial dimension of energy transition policies, practices and technologies - Caragliu, A.; Graziano, M. (Energy Policy, 2022)
Keywords: dept.mgt; peer-reviewed

Servant leadership and employee wellbeing: A crosscultural investigation of the moderated path model in Canada, Pakistan, China, the US, and Brazil - Wang, Zheni; Panaccio, Alexandra; Raja, Usman; Donia, Magda; Landry, Guylaine; Pereira, Michelle Morelo; Ferreira, Maria Cristina (International Journal of Cross Cultural Management, 2022)
Drawing on samples from Canada, Pakistan, China, the US, and Brazil comprising over 800 employees, we examined whether servant leaders (SL) - characterized as putting the needs of others above their own - promote employees’ well-being via autonomous motivation, accounting for employees’ power distance and collectivism values as moderating variables. Autonomous motivation, a type of self-regulation, sustains one’s well-being. Personal values facilitate one’s work behaviors cross-culturally. Multigroup confirmatory factor analysis (CFA) results confirmed matrix invariance of all the measures. The path and moderation analyses result using multilevel structural equation modeling (SEM) supported the positive direct and indirect paths among SL, autonomous motivation, and psychological well-being across the five cultures; Collectivistic value negatively moderated the relationship between servant leadership and autonomous motivation across the Chinese and US samples. In addition, with only a limited number of items, measurements of SL and vitality achieved scalar invariance. ANOVA test results also confirmed the significant comparative differences in these two variables among the cultural groups. Findings in this research provided robust and empirical support for the motivational effects of the servant leadership theory across the globe. Theoretical and practical implications for evidence-based cross-cultural management practices and future directions for leadership training in diverse cultural contexts are discussed.
Keywords: Servant leadership; autonomous motivation; dept.mgt; peer-reviewed; personal values; psychological well-being

A Data-Driven Algorithm to Redefine the U.S. Rural Landscape: Affinity Propagation as a Mixed-Data/Mixed-Method Tool - Heumann, Benjamin W.; Graziano, Marcello; Fiaschetti, Maurizio (Economic Development Quarterly, 2022)
This study demonstrates the application of affinity propagation as a data-driven approach to identifying and mapping typologies of place along the urban-rural continuum. The authors characterize Zip Code Tabulation Areas using demographic, economic, land cover, and accessibility to transportation infrastructure, which results in 22 clusters, 15 of which have a major rural component. The spatial pattern of these clusters varies, reflecting the heterogeneity in U.S. rurality. Rural is not a single concept that can be simply defined by population density. By comparing three economic indicators before and after the global financial crisis of 2007 to 2012, the authors find that the degree of economic recovery is captured by rural typologies. They compare both the methodological results and analysis of socioeconomic resilience to two of the most used threshold-based regional typologies, one developed by the U.S. Department of Agriculture Economic Research Service and one used by the American Communities Project.
Keywords: dept.mgt; peer-reviewed; rural data; rural demography; rural development

The many sizes and characters of the Blue Economy - Graziano, M.; Alexander, K.A.; McGrane, S.J.; Allan, G.J.; Lema, E. (Ecological Economics, 2022)
This article analyses the economic size and resilience of five established definitions of the Blue Economy across two geographical locations: Scotland (UK) and Michigan (USA). The article analyses sector-level employment, labor productivity and Gross Value Added (GVA) data, and uses graphical representations to highlight the differences in conceptualizing the Blue Economy in ways that affect its weight and contribution to regional economies. Further, it analyses how each definition has fared in the post-2007/2011 crisis, assessing their resilience. This novel work tackles the emerging discourse around the Blue Economy by highlighting its regional character, and by problematizing the divergent definitions of the concept. © 2022 Elsevier B.V.
Keywords: Blue Economy; Employment; Regional analysis; Wages; dept.mgt; peer-reviewed

Effect of a brief social contact video on transphobia and depression-related stigma among adolescents: A randomized clinical trial - Amsalem, D.; Halloran, J.; Penque, B.; Celentano, J.; Martin, A. (JAMA Network Open, 2022)
Importance: Transphobia and stigma remain barriers to seeking mental health care for gender-diverse adolescents. Objective: To examine the utility of brief social contact-based video interventions of transgender protagonists with depression to reduce transphobia and depression-related stigma and increase treatment-seeking intentions among adolescents in the general population. Design, Setting, and Participants: During August 2021, a total of 1437 participants were recruited and randomly assigned to 1 of 4 video-based conditions in a 2:2:1:1 ratio: (1) transgender adolescent girls, (2) transgender adolescent boys, (3) cisgender adolescent girls, or (4) cisgender adolescent boys. Interventions: In each of the approximately 110-second videos, an empowered presenter shared their personal story about coping with depression and reaching out for help. Main Outcomes and Measures: The primary outcome was the score on the Attitudes Toward Transgender Men and Women (ATTMW) scale. Secondary outcomes were (1) a "gender thermometer" rating for warmth in transgender perception, (2) the Depression Stigma Scale (DSS) score, and (3) the General Health-Seeking Questionnaire (GHSQ) score. Results: Of the 1437 randomized participants, 1098 (76%) completed the postintervention assessment and passed all the validity tests (mean [SD] age, 16.9 [1.2] years; 481 [44%] male; 640 [58%] White). A significant change in attitudes toward transgender youth was found within the intervention group only (mean [SD] ATTMW scores: intervention group, 34.6 [23.1] at baseline to 32.8 [24.2] after intervention; P ¡.001; control group, 33.5 [23.4] at baseline to 32.4 [24.1] after intervention; P =.01). The mean (SD) total DSS scores decreased significantly across study groups (intervention: 1.3 [3.3]; control: 1.7 [3.3]; P ¡.001). A significant increase in intention to seek help from a parent was found in the intervention (mean [SD] GHSQ score, 0.2 [1.1]) and control (mean [SD] GHSQ score, 0.3 [1.2]) groups (P ¡.001), as was a decrease in those not wanting to seek help from anyone (mean [SD] GHSQ score: intervention, 0.2 [1.6], P =.009; control, 0.3 [1.2], P ¡.001) Secondary analyses revealed significant differences in baseline ATTMW scores and intervention effects between transgender and gender-diverse and cisgender participants and between lesbian, gay, bisexual, or queer (LGBQ) and straight participants (F = 36.7, P ¡.001) and heterosexual participants (F = 37.0, P ¡.001). A significant difference was also found in mean (SD) transgender warmth scores from baseline to after intervention between groups (2.6° [13.1°] in the intervention group vs 0.4° [8.3°] in the control group; P ¡.001). Conclusions and Relevance: In this randomized clinical trial, brief social contact-based videos proved efficacious in reducing transphobia and depression-related stigma and in increasing treatment-seeking intentions among adolescents in the general population. By personifying, individualizing, and providing face and voice to the experience of transgender youth, other adolescents, especially those who are cisgender and/or of a heterosexual orientation, can gain empathetic insights into the lives of their often marginalized and stigmatized fellow youth. Trial Registration: ClinicalTrials.gov Identifier: NCT04969003. © 2022 Collabra: Psychology. All rights reserved.
Keywords: Adolescent; Depression; Female; Humans; Male; Patient Acceptance of Health Care; Prejudice; Social Stigma; Transgender Persons; Video Recording; adolescent; controlled study; depression; dept.mft; dept.swk; female; human; male; patient attitude; peer-reviewed; prejudice; psychology; randomized controlled trial; social stigma; transgender; videorecording

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

Manipulating common method variance via experimental conditions - Wall, A.E.; Simmering, M.J.; Fuller, C.M.; Waterwall, B. (Electronic Journal of Business Research Methods, 2022)
Research data collected from single respondents may raise concerns regarding common method variance (CMV), which is believed to threaten the validity of findings. The primary concern is that CMV can inflate substantive relationships, such that they appear statistically significant when they are not. Thus, understanding the nature of CMV is critical, especially when one considers the popularity—and sometimes necessity—of using self-report data. Research examining CMV has found conflicting evidence about the impact of CMV. Researchers who believe CMV influences findings have proposed solutions to combat any real or perceived potential bias, including changing survey instructions and using marker variables, but few studies have examined the efficacy of these approaches. The purpose of this study is to examine the impact of these techniques and the nature of CMV using an experimental design. To conduct the experiment, multiple versions of a survey, which vary in their use of the remedial approaches, are utilized to collect data, which resulted in 1,069 usable responses. The experimental design was based on the faking literature and included instructions intended to induce or reduce the levels of CMV. Further, two different marker variables are used to determine the degree to which they create a psychological separation in substantive variables. Correlation analysis and measurement invariance are used to analyze the data. This study posits that, if CMV is a substantial concern for self-report data and these approaches are effective, then findings will differ in surveys that incorporate such approaches from surveys that do not. Results indicate few differences in experimental conditions, meaning that regardless of instructions or marker variable, substantive item correlations remained statistically similar. The results indicate this is likely due to the minimal impact of CMV, given that the proposed methods of correction did not significantly influence research findings. These findings have implications for researchers in that they do not support that CMV, or at least its proposed remedies, significantly alter findings. However, support for the null conclusions, in spite of appropriate statistical power, warrant future research examining the nature and impact of CMV. © 2022,lectronic Journal of Business Research Methods. All Rights Reserved.
Keywords: dept.mgt; peer-reviewed